2013
DOI: 10.1097/inf.0b013e3182783dc3
|View full text |Cite
|
Sign up to set email alerts
|

Topical Umbilical Cord Care for Prevention of Infection and Neonatal Mortality

Abstract: Umbilical cord care varies often reflecting community or health-worker beliefs. We undertook a review of current evidence on topical umbilical cord care. Study quality was assessed using the Grading of Recommendations, Assessment, Development and Evaluation system, and a metaanalysis was conducted for comparable trials. Available moderate-quality to high-quality evidence indicate that cord cleansing with 4% chlorhexidine may reduce the risk of neonatal mortality and sepsis (omphalitis) in low-resource settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
63
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 23 publications
4
63
0
3
Order By: Relevance
“…The umbilical cord area supports the growth of some harmless or beneficial microorganisms (i.e., commensals) whereas others are harmful (e.g., Clostridium tetani) (Karumbi et al, 2013). Sources of these bacteria include the mother's birth canal, the environment of delivery and the hands of the person assisting with the delivery (Karumbi, et al, 2013).…”
Section: Umbilical Cord Carementioning
confidence: 99%
“…The umbilical cord area supports the growth of some harmless or beneficial microorganisms (i.e., commensals) whereas others are harmful (e.g., Clostridium tetani) (Karumbi et al, 2013). Sources of these bacteria include the mother's birth canal, the environment of delivery and the hands of the person assisting with the delivery (Karumbi, et al, 2013).…”
Section: Umbilical Cord Carementioning
confidence: 99%
“…This is also a missed opportunity because clusterrandomized trials have shown benefits of chlorhexidine application to the baby's cord and associated with decreased mortality (16,17). Use of 4% chlorhexidine has been approved to be more useful if provided to the newborn in 24 , hours of life even to apply it once is effective (18).…”
Section: Cord Carementioning
confidence: 99%
“…However, the low mortality rate and the small contribution made by bacterial infection 29 in these settings provide only a small opportunity for a reduction in mortality rates. In 5 such trials 30 -33 analyzed by Karumbi et al, 22 no treatment was found to significantly reduce omphalitis and sepsis when compared against one another, although the sample sizes were small and the evidence was deemed of low quality. 22 The Cochrane review by Imdad et al, 23 which compared a variety of pairs of topical agents, reached similar conclusions.…”
Section: Evidence-based Practicementioning
confidence: 99%
“…In 5 such trials 30 -33 analyzed by Karumbi et al, 22 no treatment was found to significantly reduce omphalitis and sepsis when compared against one another, although the sample sizes were small and the evidence was deemed of low quality. 22 The Cochrane review by Imdad et al, 23 which compared a variety of pairs of topical agents, reached similar conclusions. The most recent meta-analysis, by Sinha et al, 24 considered 2 studies 28, 34 comparing chlorhexidine with dry cord care.…”
Section: Evidence-based Practicementioning
confidence: 99%